SETD3 Methyltransferase Regulates PLK1 Expression to Promote In Situ Hepatic Carcinogenesis - Cheng, Meng; Yang, Qingmiao; Liu, Yafei; Zhao, Meng-Jie; Du, Xinyuan; Sun, Jiaqi; Shu, Wen-Jie; Huang, Zan; Bi, Jianping; Xu, Ximing; Du, Hai-Ning (Frontiers in Oncology, 2022)
Background: Development of new strategy to overcome chemoresistance of hepatocellular carcinoma (HCC) treatment is a long-standing issue.We have previously found that upregulated SETD3 levels are closely correlated with HCC. This study aims to explore the mechanism underlying how upregulation of SETD3 promotes liver carcinogenesis. Methods: RNA-Sequencing analysis was used to explore the correlation of SETD3 with regulatory targets. In vitro assays including cell proliferation, migration and invasion were performed to study the oncogenic roles of SETD3 and Plk1. Western blotting, immunohistochemical staining and blood biochemical assays were performed to examine protein expression or pathological index in tumor tissues and mice liver tissues. Luciferase reporter system and chromatin immunoprecipitation assays were used to explore the mechanism. Results: We revealed that SETD3 regulates gene expression in subgroups, including cell division, cell proliferation, and cell cycle, in hepatocellular tumor cells. We found that SETD3 upregulation is associated with elevated Plk1 level in both hepatic tumor cells and clinical liver tissues. We further showed that overexpression of SETD3 promoted tumor cell proliferation, migration and invasiveness, whereas inhibition of Plk1 activity attenuated these phenotypes caused by SETD3. By taking advantage of the Sleep Beauty transposase system, we confirmed that upregulated SETD3 promoted hepatic carcinogenesis in situ, but knockdown of PLK1 mitigated SETD3-promoted tumorigenesis in mice. Mechanistically, we showed that SETD3 could be recruited to the promoter of PLK1 gene to facilitate PLK1 transcription. Conclusions: Our data demonstrate that elevated SETD3 may promote HCC by enhancing Plk1 expression, which suggests that SETD3 may act as a potential drug target combined with Plk1 inhibition to treat HCC.